Can Early Warning Systems Enhance Detection of High Risk Patients by Rapid Response Teams?. (May 2021) - Reardon, Peter M.; Seely, Andrew J. E.; Fernando, Shannon M.; Didcote, Simon; Strachan, Iain; Baudino, Jean-Loup; Kyeremanteng, Kwadwo
Purpose: We sought to evaluate if incorporating an early warning system (EWS), the Visensia Safety Index (VSI) and the National Early Warning Systems 2 (NEWS2), may lead to earlier identification of rapid response team (RRT) patients. Methods: This was a retrospective study (2015-2018) of patients experiencing RRT activation within a tertiary care network. We evaluated the proportion of patients with an EWS alert prior to RRT activation and their associated outcomes (primary: hospital mortality). Results: There were 6, 346 RRT activations over the study period. Of these, 2042 (50.8%) patients would have had a VSI alert prior to RRT activation, with a median advanced time of 3.6 (IQR 0.5-12.8) hours, compared to 2351 (58.4%) patients and 9.8 (IQR 2.0-18.7) hours for NEWS2. Patients with a potential alert prior to RRT activation had an increased odds of mortality for both VSI (OR 1.2, 95%CI 1.1-1.3) and NEWS2 (OR 2.7, 95% CI 2.4-3.1). Prognostic accuracy for hospital mortality was similar between groups. Conclusion: Utilization of an EWS by an RRT has potential to provide earlier recognition of deterioration and mortality risk among hospitalized inpatients.